Polyunsaturated Fatty Acids in Atrial Fibrillation: Looking for the Proper Candidates - Salvador-Montañés, Oscar; Gómez-Gallanti, Alfonso; Garofalo, Daniel; Noujaim, Sami F.; Peinado, Rafael; Filgueiras-Rama, David (Frontiers in Physiology, 2012)
Atrial fibrillation (AF) is the most common sustained arrhythmia encountered in clinical practice with growing prevalence in developed countries. Several medical and interventional therapies, such as atrial specific drugs and pulmonary vein isolation, have demonstrated prevention of recurrences. However, their suboptimal long-term success and significant rate of secondary effects have led to intensive research in the last decade focused on novel alternative and supplemental therapies. One such candidate is polyunsaturated fatty acids (PUFAs). Because of their biological properties, safety, simplicity and relatively cheap cost, there is a special clinical interest in omega-3 PUFAs as a possible anti-arrhythmic agent. Obtained from diets rich in fish, they represent one of the current supplemental therapies. At the cellular level, an increasing body of evidence has shown that n-3 PUFAs exert a variety of effects on cardiac ion channels, membrane dynamic properties, inflammatory cascade and other targets related to AF prevention. In this article, we review the current basic and clinical evidence pertinent to n-3 PUFAs in AF treatment and prevention. We also discuss controversial outcomes among clinical studies and propose specific subsets of AF patients who will benefit most from n-3 PUFAs.